PRESERVING THE INDIGENOUS MUSICAL INSTRUMENTS OF PAPUAN USING AUGMENTED REALITY TECHNOLOGY - Khosin, Noor; Dedi I Inan; Ratna Juita; Muhamad Indra (Universitas Serang Raya, 2025)
This study explores the use of augmented reality (AR) technology as a technology enabling the preservation of traditional Papua musical instruments. It aims of understanding factors that influence the adoption of this technology by people living in Papua who are not indigenous Papuans. The use of AR as a tool for cultural preservation is still limited, particularly in the context of Papua, highlighting a research gap concerning the acceptance of AR technology in regions rich in culture but limited in technology adoption. The study employs Design Science Research (DSR) as a research framework. The development and evaluation in the DSR are conducted rigorously and robustly. Once the AR artifact is developed using uniteAR tool, subsequently it is evaluated employing UTAU2 as a theoretical lens. Particularly in the evaluation stage, it involves 115 respondents as participants in data collection. The data is analyzed with partial least square structural equation modeling (PLS-SEM). The main findings indicate that the measurement model has good reliability and validity, with an R² value of 0.8, meaning that Behavioral Intention and Use Behavior explain 80% of the variability in AR technology adoption. The findings also reveal that performance expectancy, effort expectancy, and facilitating conditions are significant factors driving AR technology adoption among respondents. The implications of this study are highly relevant for the development of strategies using AR technology to introduce and preserve traditional Papua musical instruments. These findings can be used by local governments, indigenous communities, and local content developers to design more effective solutions for enhancing AR adoption in Papua, taking into account key factors influencing public behavioral intentions. Thus, this research not only provides theoretical insights into technology adoption but also strengthens the integration of culture and technology in Papua, opening opportunities for more interactive and engaging cultural preservation. Keywords: Technology Adoption, Augmented Reality, Papua Traditional Musical Instruments, PLS-SEM, UTAUT